Decorative material for wall surface based on dredged sand

By combining dredged sand with nanophotocatalyst and modified zeolite powder, a nanophotocatalyst-enhanced wall decorative material was prepared, which solved the shortcomings of traditional materials in environmental protection and functionality, and achieved efficient use of dredged sand and improved air Purification and physical performance effects.

CN119286290APending Publication Date: 2025-01-10镇江市港发绿色资源有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411601137.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional wall decorative materials have shortcomings in environmental protection, resource utilization and functionality. In particular, dredged sand is a by-product. Its utilization efficiency is low and improper treatment may lead to environmental pollution, and it is technically difficult to use directly as building materials.

Method used

Using dredged sand as the basic material, combined with polymer adhesives, curing agents, nanophotocatalysts, nanoadsorbents, dispersants, stabilizers, pH regulators and functional pigments, a nanometer is prepared through specific mixing and processing steps. Photocatalyst-enhanced decorative materials utilize the adsorption capacity of nanophotocatalysts and modified zeolite powder to enhance air purification and self-cleaning functions.

Benefits of technology

Effectively reduce the demand for natural sand, improve the environmental friendliness of building materials, enhance the air purification function, improve the compressive strength and flexural strength of decorative materials, ensure the durability and stability of wall decorative materials. Reduced environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128343080000071
    Figure BDA0005128343080000071
Patent Text Reader

Abstract

The invention discloses a decorative material for a wall surface based on dredged sand. The decorative material comprises the following components: dredged sand, polyvinyl alcohol, sodium silicate, titanium dioxide nanoparticles, modified zeolite powder, a nonionic surfactant, an organic silicon antioxidant, sodium carbonate and a functional pigment which are mixed according to a specific weight percentage ratio. The dredged sand is used as a base material, and the polymer adhesive and the curing agent are combined, so that the basic form and physical properties of the decorative material are provided. By adding the nano photocatalyst and the nano adsorption material, the decorative material is endowed with the functions of self-cleaning and environment purification. Due to the introduction of the functional pigment, a light-induced or heat-induced color change effect is provided for the product. The decorative material has excellent environment-friendly characteristics and physical properties, and can achieve good balance between environment friendliness and functionality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coating, and more particularly to a decorative material for walls based on dredged sand. Background Art

[0002] In recent years, with the increasing awareness of environmental protection and the rapid development of the construction industry, the performance requirements for building decoration materials have become increasingly higher. Wall decoration materials need to be not only beautiful and durable, but also environmentally friendly and functional. However, traditional wall decoration materials such as latex paint and wallpaper, although they can meet basic needs in terms of aesthetics and applicability, often have deficiencies in environmental protection, resource utilization and functionality.

[0003] In terms of resource utilization, dredged sand is a byproduct produced in large quantities during river dredging, port maintenance and water management. Its utilization efficiency is low and improper handling can cause secondary pollution to the environment. Due to its complex composition, high organic content, fine particles and uneven distribution, it is relatively difficult to use it directly as a building material. Therefore, how to effectively use dredged sand as a wall decoration material is a difficult problem currently faced. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a decorative material for walls based on dredged sand, and the specific scheme is as follows:

[0005] A decorative material for walls based on dredged sand, comprising the following components by weight percentage:

[0006] Basic material: dredged sand 60-75%;

[0007] Polymer adhesive: polyvinyl alcohol 3-8%;

[0008] Curing agent: sodium silicate 1-3%;

[0009] Nano photocatalyst: 1-5% titanium dioxide nanoparticles;

[0010] Nano adsorption material: modified zeolite powder 0.5-2%;

[0011] Dispersant: nonionic surfactant 0.1-0.5%;

[0012] Stabilizer: silicone antioxidant 0.1-0.5%;

[0013] pH adjuster: Sodium carbonate, added according to pH requirements to maintain the pH value of the mixture at 8-10;

[0014] Functional pigments: photochromic pigments or thermochromic pigments 0.2-2%.

[0015] Furthermore, the preparation process of the decorative material comprises the following steps:

[0016] S1. Premixing: First, mix the dredged sand and dispersant evenly at room temperature;

[0017] S2. Dissolution and activation: under stirring conditions, deionized water is gradually added to dissolve the polyvinyl alcohol, and modified zeolite powder is added to activate the adsorption material;

[0018] S3, pH adjustment: adding sodium carbonate to adjust the pH value of the mixture to weak alkalinity;

[0019] S4, adding curing agent and photocatalyst: adding sodium silicate and titanium dioxide nanoparticles to start the curing reaction;

[0020] S5. Addition of functional pigments: evenly dispersing photochromic or thermochromic pigments in the mixture;

[0021] S6. Stirring and mixing: fully mix the added materials to form a uniform decorative material slurry;

[0022] S7, molding and curing: pour the mixture into a mold and let it stand for the curing reaction to complete, which takes about 24 to 48 hours;

[0023] S8. Drying: Dry the solidified material until the moisture content is less than 3%.

[0024] Further, the modified zeolite powder comprises the following steps:

[0025] S1. Choose the right zeolite raw material: Choose natural zeolite powder with a particle size of 2-5 microns as the raw material

[0026] S2, pickling treatment: zeolite powder is mixed with 5%-10% dilute hydrochloric acid solution at a mass ratio of 1:5, the reaction temperature is controlled at 50-70°C, and the reaction time is 1-2 hours;

[0027] S3, filtering and washing: filtering the acid-washed zeolite powder and washing with deionized water to a neutral pH value;

[0028] S4, drying: drying the washed zeolite powder at 105° C. for 12 hours to obtain dry zeolite powder;

[0029] S5, organic modification: mixing the dried zeolite powder with trimethylchlorosilane at a mass ratio of 0.1-0.5%;

[0030] S6. Heat treatment: heat treating the modified zeolite powder at 150-200° C. for 2-3 hours;

[0031] S7. Cooling and pulverizing: The heat-treated zeolite powder is naturally cooled to room temperature, and then the particle size is adjusted to 1-3 microns by mechanical grinding.

[0032] Furthermore, when S5 is organically modified, the reaction temperature is 60-80°C and the reaction time is 2-4h.

[0033] Furthermore, the particle size of the nano-photocatalyst titanium dioxide is 10 to 20 nanometers.

[0034] Furthermore, the surface of the modified zeolite powder is subjected to organic modification treatment to improve its adsorption capacity and selectivity for toxic and harmful substances.

[0035] Furthermore, the method for using the decorative material on the wall comprises the following steps:

[0036] S1. Prepare mixed slurry: prepare uniform decorative material slurry according to the proportions and steps in claims 1 to 5;

[0037] S2. Construction: Apply the prepared slurry to the wall surface by spraying, scraping or printing, and ensure uniform distribution;

[0038] S3. Photocatalyst activation: Under natural light or UV light, titanium dioxide nanoparticles form photocatalytic activity;

[0039] S4, drying and curing: curing is carried out under constant temperature and humidity conditions for 24 to 72 hours;

[0040] S5. Quality inspection and modification: Carry out quality inspection on the wall after construction to ensure there are no defects such as color difference and cracks, and modify and improve the necessary parts.

[0041] Beneficial effects:

[0042] (1) By using dredged sand as the base material, this patent not only effectively reduces the demand for natural sand in building materials and alleviates the mining pressure, but also realizes the efficient utilization of dredged sand waste and reduces environmental pollution.

[0043] (2) Nano-photocatalysts such as titanium dioxide nanoparticles are added. These nanoparticles can decompose indoor harmful gases such as formaldehyde and benzene under the action of light, improve air quality, and have good environmental purification functions. The surface of the decorative material has a self-cleaning function under the action of nano-photocatalysts, which can effectively decompose adsorbed organic pollutants and reduce the cleaning and maintenance workload of the wall.

[0044] (3) At the same time, organic functional groups are introduced into the surface of the zeolite powder after organic modification, which can provide more active sites and increase the adsorption capacity for specific harmful gas molecules, thereby improving the overall air purification effect.

[0045] (4) It can be seen from the test data that the compressive strength and flexural strength of the decorative material obtained by the present invention are higher than those of traditional decorative materials, showing excellent physical properties and being able to ensure the durability and stability of the wall decorative material. DETAILED DESCRIPTION

[0046] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0047] Example 1

[0048] Group distribution ratio

[0049] Base material: dredged sand 70%

[0050] Polymer adhesive: polyvinyl alcohol 5%

[0051] Curing agent: sodium silicate 2%

[0052] Nano photocatalyst: Titanium dioxide nanoparticles 3%

[0053] Nano adsorption material: modified zeolite powder 1%

[0054] Dispersant: Nonionic surfactant 0.3%

[0055] Stabilizer: Silicone antioxidant 0.2%

[0056] pH adjuster: Sodium carbonate, add to pH 9

[0057] Functional pigment: photochromic pigment 1%

[0058] Preparation steps

[0059] 1. Premixing (S1): Mix dredged sand and nonionic surfactant and stir for 5 minutes at room temperature to form a uniform matrix.

[0060] 2. Dissolution and activation (S2): Deionized water was gradually added to the matrix to dissolve the polyvinyl alcohol, and modified zeolite powder was added to enhance the adsorption performance, and stirred for 20 minutes.

[0061] 3. pH adjustment (S3): Add sodium carbonate and monitor the pH value of the solution to 9 to maintain a weak alkaline environment.

[0062] 4. Adding curing agent and photocatalyst (S4): adding sodium silicate and titanium dioxide nanoparticles, continuing stirring, and performing curing reaction.

[0063] 5. Functional pigment addition (S5): Add photochromic pigment evenly to ensure color change effect.

[0064] 6. Stirring and mixing (S6): Stir thoroughly for 15 minutes to ensure a uniform material slurry.

[0065] 7. Molding and curing (S7): Pour the mixture into a mold and let it stand for 24 hours until it is completely cured.

[0066] 8. Drying treatment (S8): The solidified material is dried at 60°C until the moisture content is less than 3%.

[0067] Example 2

[0068] Group distribution ratio

[0069] Base material: dredged sand 65%

[0070] Polymer adhesive: polyvinyl alcohol 6%

[0071] Curing agent: sodium silicate 1.5%

[0072] Nano photocatalyst: Titanium dioxide nanoparticles 4%

[0073] Nano adsorption material: modified zeolite powder 2%

[0074] Dispersant: Nonionic surfactant 0.4%

[0075] Stabilizer: Silicone antioxidant 0.3%

[0076] pH adjuster: Sodium carbonate, add to pH 8.5

[0077] Functional pigment: Thermochromic pigment 1.5%

[0078] Preparation steps

[0079] 1. Premixing (S1): Mix the dredged sand and dispersant at room temperature and stir for 10 minutes until uniform.

[0080] 2. Dissolution and activation (S2): Deionized water was added to dissolve the polyvinyl alcohol, and modified zeolite powder was added to activate its adsorption performance, and stirred for 25 minutes.

[0081] 3. pH adjustment (S3): gradually add sodium carbonate to adjust the pH value to 8.5.

[0082] 4. Adding curing agent and photocatalyst (S4): adding sodium silicate and titanium dioxide nanoparticles to make the mixture evenly dispersed.

[0083] 5. Functional pigment addition (S5): Add thermochromic pigments to ensure the dynamic effect of color under temperature changes.

[0084] 6. Stirring and mixing (S6): Continue stirring for 20 minutes to obtain a uniform slurry.

[0085] 7. Molding and curing (S7): The mixture is poured into a mold and left to stand for 48 hours to complete curing.

[0086] 8. Drying (S8): Drying with hot air at 80°C until the moisture content is less than 3%.

[0087] Example 3

[0088] Group distribution ratio

[0089] Base material: dredged sand 75%

[0090] Polymer adhesive: polyvinyl alcohol 4%

[0091] Curing agent: sodium silicate 3%

[0092] Nano photocatalyst: Titanium dioxide nanoparticles 2%

[0093] Nano adsorption material: modified zeolite powder 0.8%

[0094] Dispersant: Nonionic surfactant 0.2%

[0095] Stabilizer: Silicone antioxidant 0.4%

[0096] pH adjuster: Sodium carbonate, adjusted to pH 10

[0097] Functional pigment: photochromic pigment 2%

[0098] Preparation steps

[0099] 1. Premixing (S1): Mix the dredged sand with the dispersant and stir for 5 minutes to ensure uniformity.

[0100] 2. Dissolution and activation (S2): Add deionized water to dissolve polyvinyl alcohol, add 0.8% modified zeolite powder, and stir for 30 minutes.

[0101] 3. pH adjustment (S3): Sodium carbonate was added to adjust the pH value of the mixture to 10.

[0102] 4. Adding curing agent and photocatalyst (S4): Add sodium silicate and titanium dioxide nanoparticles with a particle size of 15 nanometers, and continue stirring until uniform.

[0103] 5. Functional pigment addition (S5): Photochromic pigments are added to enhance the decorative effect.

[0104] 6. Stirring and mixing (S6): Stir evenly to make all components evenly distributed.

[0105] 7. Molding and curing (S7): Pour into the mold and let stand for 24 hours to ensure complete curing.

[0106] 8. Drying treatment (S8): Dry the solidified material at 70°C to control the moisture content to less than 3%.

[0107] The performance of the decorative materials obtained in Examples 1 to 3 was compared with the traditional decorative materials in the comparative example. The comparative data are as follows:

[0108]

[0109]

[0110] In summary, the decorative material obtained in the embodiment has been significantly improved in mechanical properties and self-cleaning properties.

[0111] As a further improvement, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A decorative material for walls based on dredged sand, characterized in that: Calculated by weight percentage, it includes the following components: Basic material: dredged sand 60-75%; Polymer adhesive: polyvinyl alcohol 3-8%; Curing agent: sodium silicate 1-3%; Nano photocatalyst: 1-5% titanium dioxide nanoparticles; Nano adsorption material: modified zeolite powder 0.5-2%; Dispersant: nonionic surfactant 0.1-0.5%; Stabilizer: silicone antioxidant 0.1-0.5%; pH adjuster: Sodium carbonate, added according to pH requirements to maintain the pH value of the mixture at 8-10; Functional pigments: photochromic pigments or thermochromic pigments 0.2-2%.

2. A decorative material for wall based on dredged sand according to claim 1, characterized in that: The preparation process of the decorative material comprises the following steps: S1. Premixing: First, mix the dredged sand and dispersant evenly at room temperature; S2. Dissolution and activation: under stirring conditions, deionized water is gradually added to dissolve the polyvinyl alcohol, and modified zeolite powder is added to activate the adsorption material; S3, pH adjustment: adding sodium carbonate to adjust the pH value of the mixture to weak alkalinity; S4, adding curing agent and photocatalyst: adding sodium silicate and titanium dioxide nanoparticles to start the curing reaction; S5. Addition of functional pigments: evenly dispersing photochromic or thermochromic pigments in the mixture; S6. Stirring and mixing: fully mix the added materials to form a uniform decorative material slurry; S7, molding and curing: pour the mixture into a mold and let it stand for the curing reaction to complete, which takes about 24 to 48 hours; S8. Drying: Dry the solidified material until the moisture content is less than 3%.

3. A decorative material for wall based on dredged sand according to claim 1, characterized in that: Modified zeolite powder comprises the following steps: S1. Choose the right zeolite raw material: Choose natural zeolite powder with a particle size of 2-5 microns as the raw material S2, pickling treatment: zeolite powder is mixed with 5%-10% dilute hydrochloric acid solution at a mass ratio of 1:5, the reaction temperature is controlled at 50-70°C, and the reaction time is 1-2 hours; S3, filtering and washing: filtering the acid-washed zeolite powder and washing with deionized water to a neutral pH value; S4, drying: drying the washed zeolite powder at 105° C. for 12 hours to obtain dry zeolite powder; S5, organic modification: mixing the dried zeolite powder with trimethylchlorosilane at a mass ratio of 0.1-0.5%; S6. Heat treatment: heat treating the modified zeolite powder at 150-200° C. for 2-3 hours; S7. Cooling and pulverizing: The heat-treated zeolite powder is naturally cooled to room temperature, and then the particle size is adjusted to 1-3 microns by mechanical grinding.

4. A decorative material for wall based on dredged sand according to claim 1, characterized in that: The particle size of the nanometer photocatalyst titanium dioxide is 10 to 20 nanometers.

5. A decorative material for wall based on dredged sand according to claim 3, characterized in that: When S5 is organically modified, the reaction temperature is 60-80°C and the reaction time is 2-4h.

6. A decorative material for wall based on dredged sand according to claim 1, characterized in that: The method used on the wall includes the following steps: S1. Prepare mixed slurry: prepare uniform decorative material slurry according to the proportions and steps in claims 1 to 5; S2. Construction: Apply the prepared slurry to the wall surface by spraying, scraping or printing, and ensure uniform distribution; S3. Photocatalyst activation: Under natural light or UV light, titanium dioxide nanoparticles form photocatalytic activity; S4. Drying and curing: Curing is carried out under constant temperature and humidity conditions.

Citation Information

Patent Citations

  • Environmental-friendly texture coating composition and preparation method thereof

    CN104449096A

  • Nano self-cleaning type stone-like coating and preparation method thereof

    CN105949911A

  • Thermal insulation gypsum mortar based on synergistic effect of dredged sand and aerogel

    CN117843328A